Stretching-insensitive stretchable and biocompatible triboelectric nanogenerators using plasticized PVC gel and graphene electrode for body-integrated touch sensor. (March 2023) - Kim, Mingyu; Park, Hyosik; Lee, Mun Hwan; Bae, Jin Woo; Lee, Keun Young; Lee, Ju Hun; Lee, Ju-Hyuck
Abstract: Triboelectric nanogenerators (TENG) can generate strong electrical signals even with low frequencies and weak forces, thus research has been conducted to use them as wearable, body-attachable, and body-embeddable devices using biomechanical energies. For this reason, the TENG components, such as dielectric materials and electrodes, should be stretchable. A stretchable and biocompatible single electrode TENG based on plasticized polyvinyl chloride (PVC) gel with a graphene electrode is fabricated. PVC gel is a suitable stretchable TENG dielectric material owing to its high stretchability, dielectric constant, and tribo-negative properties, and graphene is a highly conductive electrode. Graphene and PVC gel-based stretchable and biocompatible TENGs display excellent electrical outputs (48 V, 2.5 μA, and 0.49 W/ m 2 ). The electrical resistance range of the electrode which does not affect the TENG output performance, and a stretching-insensitive TENG with approximately 50% stretching rate is successfully demonstrated through this study. In addition, both PVC gel and graphene are biocompatible. These stretching-insensitive and biocompatible TENGs may be used as a self-powered touch sensor that can be integrated into the human body. Graphical Abstract: A PVC gel/graphene layer was designed and optimized for stretching insensitive stretchable and biocompatible triboelectric nanogenerator (TENG). A TENG that generates stable output up to 50% of stretched condition was developed by analyzing the electrical resistance range of the electrode that affects the output performance. The proposed TENG can be applied to future e-skin or wearable devices. ga1 Highlights: We report stretching insensitive biocompatible TENG based on graphene electrodes and PVC gel. TENG generates stable output up to 50% of stretched condition. Electrical resistance range of the electrode that does not affects the output performance of the TENG is analyzed. The self-powered skin-like TENG shows promising potential in future wearable and biomedical applications.